Pemanfaatan objek wisata Istana Maimun sebagai peninggalan sejarah Kesultanan Deli di Medan dalam mendukung Pariwisata Sumatera Utara - Donargo, Sepdwiyana (Politeknik Pariwisata Medan, 2023)
Tourism is a sector that is highly relied on in national development because tourism can increase national income and regional and state income. Regarding the development of Indonesian tourism, the Visit Indonesia program, which was launched in 2008 and has been continued until now, has brought new enthusiasm to the tourism community in Indonesia. Through efforts and improvement of services, supported by improved security situation, as well as recovery from the global economic crisis experienced by many European countries, the statistics of foreign tourist arrivals (tourists) to Indonesia in 2016 experienced a significant increase compared to the previous year. From 2016 to September the number of foreign tourists visiting Indonesia reached 8.4 million, an increase of 10.53 percent. (Ministry of Tourism, 2016) Knowing how far it can be used as a tourist attraction in Medan City So that historical heritage can be functioned/made as a tourist object To be able to increase foreign and local tourist visits to the Maimoon palace to support tourism in North Sumatra. This research was carried out using a qualitative approach in this case based on the intention to describe the historical heritage of the Sultan of Deli Maimun in its utilization to support tourism in North Sumatra. Maimun Palace as a legacy of the Deli Malay Sultanate has good potential to become a point of interest. The point of beauty of the palace is an attraction besides the beauty of the building, the convenience of the intention is also an added value for the Maimun Palace, the dots of the Maimun Palace are an attraction for visitors to want to know more about Maimun Palace. To the management of the Maimun Palace, the publication always maintains the unique values contained in the Maimun Palace to the local government of Medan City and its staff, the Medan City Tourism Office continues to encourage efforts to preserve Maimun Palace.